Divorce Petitions by Female PPPK Employees in Indonesia: A Socio-Legal Analysis of Legal Empowerment and Cultural Transformation - Jamilah, Fitrotin (VRISPRAAK : International Journal of Law, 2025)
This article aims to analyze the phenomenon of divorce petitions filed by wives working as Government Employees with Work Agreements (Pegawai Pemerintah dengan Perjanjian Kerja or PPPK) through a socio-legal perspective. The study is designed as a literature-based research that explores the increasing trend of divorce initiated by PPPK wives as a distinctive socio-legal phenomenon in contemporary Indonesia. The significance of this research lies in its attempt to interpret the issue not merely from a normative legal standpoint but as a complex interaction between economic independence, social mobility, and the transformation of legal culture. The status of PPPK acts as a catalyst for women’s legal empowerment, providing them with access to financial resources, information, and social networks that enhance their legal capability. Using Lawrence M. Friedman’s legal system theory, this study finds that the shifting legal culture among PPPK wives from a culture of endurance to a culture of exit serves as the primary driver activating the substantive and structural components of divorce law. The research concludes that divorce petitions by PPPK wives represent a form of agency and legal empowerment among modern Indonesian women, reflecting the dynamic interaction between law and changing socio-economic structures. Strengthening gender-sensitive legal awareness and responsive family law policies is therefore essential to accommodate this evolving social reality.